2006
DOI: 10.1108/17410400610671453
|View full text |Cite
|
Sign up to set email alerts
|

Motivation model for improving productivity in a manufacturing unit – a success story

Abstract: PurposeThe purpose of this paper is to provide a useful motivational scheme for a practicing manager to improve the performance of a manufacturing unit.Design/methodology/approachIn this paper, the main causes for the present low productivity of the manufacturing unit are analysed and a multi‐factor group incentive scheme is designed for motivating the employees in order to improve the productivity of a manufacturing unit.FindingsThis paper provides information about various factors having a bearing on product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Rao (2006) in his research measures the production of urea and nitrogen. Then he implemented group's motivation in the organization and ultimately measures productivity again [19]. The results of his research show that production level increases by motivation increment.…”
Section: Research Literaturementioning
confidence: 78%
“…Rao (2006) in his research measures the production of urea and nitrogen. Then he implemented group's motivation in the organization and ultimately measures productivity again [19]. The results of his research show that production level increases by motivation increment.…”
Section: Research Literaturementioning
confidence: 78%
“…Rao in his research measures the production of urea and nitrogen and then implemented group's motivation in the organization and ultimately measures productivity again (Rao, 2006). The results show that production level increases by motivation increment.…”
Section: International Journal Of Research Studies In Managementmentioning
confidence: 98%
“…Behavioural scientists have found that effective motivation has positive effects on organisational performance in manufacturing enterprises (Rao, 2005). Organisational performance depends largely upon workers' commitment and engagement.…”
Section: Organisational Behaviourmentioning
confidence: 99%